The CRISPR/Cas9-Mediated Knockout of VgrG2 in Wild Pathogenic E. coli to Alleviate the Effects on Cell Damage and Autophagy - Tian-Ling Pan; Jin-Long Cha; Hao Wang; Jing-Song Zhang; Jin-Long Xiao; Jue Shen; Meng Zhou; Yue Li; Jin-Zhi Ma; Kai-Yuan Zhao; Yong-Kang Zhang; Peng Xiao; et al. (Veterinary Sciences)
CRISPR/Cas9, as a well-established gene editing technology, has been applied in numerous model organisms, but its application in wild-type E. coli remains limited. Pathogenic wild-type E. coli, a major cause of foodborne illnesses and intestinal inflammation in humans and animals, poses a significant global public health threat. The valine-glycine repeat protein G (VgrG) is a key virulence factor that enhances E. coli pathogenicity. In this study, PCR was used to identify 50 strains carrying the virulence gene VgrG2 out of 83 wild pathogenic E. coli strains, with only one strain sensitive to kanamycin and spectinomycin. A homologous repair template for VgrG2 was constructed using overlap PCR. A dual-plasmid CRISPR/Cas9 system, combining pTarget (spectinomycin resistance) and pCas (kanamycin resistance) with Red homologous recombination, was then used to induce genomic cleavage and knock out VgrG2. PCR and sequencing confirmed the deletion of a 1708 bp fragment of the VgrG2 gene in wild-type E. coli. IPEC-J2 cells were infected with E. coli-WT and E. coli ∆VgrG2, and treated with the mTOR inhibitor rapamycin to study the effects of VgrG2 on the mTOR signaling pathway. The qPCR results showed that VgrG2 activated the mTOR pathway, suppressed mTOR and p62 mRNA levels, and upregulated the autophagy-related genes and LC3-II protein expression. In conclusion, we utilized CRISPR/Cas9 technology to achieve large-fragment deletions in wild-type E. coli, revealing that VgrG2 activates the mTOR signaling pathway and upregulates autophagy markers. These findings offer new insights into E. coli genome editing and clarifies the pathogenic mechanisms through which VgrG2 induces cellular damage.